(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
The research aimed to examine the moderating role of impression management in the relationship between environmental disclosure and investor sentiment. It analyzed the annual financial reports of a sample of ten banks listed on the Iraq Stock Exchange for the period 2014–2023. The findings indicate that environmental disclosure has a significant impact on investor sentiment, and that impression management practices moderate and partially diminish this effect.